INVESTIGATION INTO ACCOUNT OF A TIME VALUE OF MONEY IN CLASSICAL MULTITOPIC INVENTORY MODELS - Natalya A. Chernyaeva; Vladimir F. Shishov (Статистика и экономика)
The article describes two types of models. The first is a traditional multitopic inventory model with constant demand and the second is a model based on the average cost of inventory in optimizing inventory management system. The authors taking into account the time value of money in the models study three possible schemes for the payment of costs: «prenumerando» (at the time of the general batch order delivery), «postnumerando» (at the time of the general next batch order delivery) and the scheme of payment of costs in the mid-term.Maximization of the total intensity of revenue for outgoing and incoming cash flows occurring in the inventory management system that characterize the analyzed models was adopted as the criterion of optimization of inventory control strategy.